Mean arterial pressure after out-of-hospital cardiac arrest (METAPHORE): study protocol for a multicentre controlled trial with blinded primary outcome assessor - Cédric Bruel; Christophe Guitton; Jean-Pierre Frat; Jeremy Bourenne; Guylaine Labro; Jean-Pierre Quenot; Gwenhaël Colin; Arnaud W Thille; Christophe Guervilly; Kada Klouche; Laurence Dangers; Jean Reignier; et al. (BMJ Open)
Introduction Out-of-hospital cardiac arrest is a public health concern with a high mortality rate. Hypoxic ischaemic brain injury is the primary cause of death in patients admitted to the intensive care unit (ICU) after return of spontaneous circulation (ROSC). Several systemic factors, such as hypotension, can exacerbate brain injuries. International guidelines recommend targeting a mean arterial pressure (MAP) of at least 65 mm Hg. Several observational studies suggest that a higher MAP may be associated with better outcomes, but no randomised trials have shown an effect of higher MAP. The ongoing METAPHORE (mean arterial pressure after out-of-hospital cardiac arrest) trial aims to compare a standard MAP threshold (MAP ≥65 mm Hg) with a high MAP threshold (MAP ≥90 mm Hg) to evaluate whether implementing a higher MAP threshold can improve neurological outcomes in patients admitted to ICU after cardiac arrest.Methods and analysis METAPHORE is a randomised, controlled, multicentre, open-label trial with a blinded primary outcome assessor, comparing two parallel groups of patients 18 years of age or older, receiving invasive mechanical ventilation for coma defined by a Glasgow Coma Score ≤8/15 after out-of-hospital cardiac arrest and sustained ROSC. Eligible patients are randomly assigned in a 1:1 ratio to either a MAP target threshold of 65 mm Hg or higher throughout the ICU stay (control group) or a MAP target threshold of 90 mm Hg or higher during the first 24 hours after randomisation, followed by 65 mm Hg or higher for the remainder of the ICU stay (intervention group). Both groups receive the same general care concerning post-cardiac arrest syndrome management according to international guidelines. The primary endpoint is the proportion of patients with a favourable neurological outcome as defined by a modified Rankin scale (mRS) of 0 to 3 measured on day 180 after inclusion by a psychologist blinded to the allocation of the intervention. Secondary outcomes are the proportion of patients alive at ICU and hospital discharge, at day 28 and day 180; proportion of patients alive at ICU discharge with a mRS of 0 to 3; the EuroQOL-5D-5L at day 180; the Clinical Frailty Scale at day 180; the number of ICU-free days, ventilator-free days, catecholamine-free days and renal replacement therapy-free days at day 28; the proportion of patients with acute kidney injury stage 3 and need for renal replacement therapy within ICU stay and proportion of patients with persistent need for renal replacement therapy at ICU discharge; and safety outcomes (cardiovascular, neurological, cutaneous, digestive and haemorrhagic complications within 7 days after inclusion). Subgroup analyses are planned according to initial cardiac arrest rhythm (shockable or non-shockable), chronic hypertension and Cardiac Arrest Hospital Prognosis score. Outcomes will be analysed on an intention-to-treat basis. Recruitment started in October 2024 in 27 French ICUs, and a sample of 1380 patients is expected by October 2027.Ethics and dissemination The study received approval from the national ethics review board on 8 February 2024 (Comité de Protection des Personnes Sud-Est V – 2023-A00257-38). Patients are included after informed consent has been obtained either from a proxy or through an emergency procedure. Results will be submitted for publication in peer-reviewed journals.Trial registration number ClinicalTrials.gov: NCT05486884.